Transanal Minimally Invasive Surgery (TAMIS) Using Single Incision Laparoscopic Surgery (SILS) Port for the Management of Benign Rectal Neoplasms: A Single Center Study - UPRAK, TEVFİK KIVILCIM; ATALAY, VAFİ (My University, 2021)
Aim: Conventional transanal excision was described decades ago for treatment of benign rectal neoplasms. However, the chalanges of this technique leads to use alternative approachs. We evaluated the results of transanal minimally invasive surgery (TAMIS) with single incision laparoscopic surgery (SILS) port in treatment of benign rectal neoplasms. Method: Data of the patients who underwent TAMIS with SILS port in one center were retrospectively analyzed. SILS port was placed through in the anal canal and ultrasonic sealing device was used for excision the tumors. Complications during or after surgery were reported. Patients were followed-up by rectal examination with rectoscopy and recurrences were evaluated. Results: Between July 2015 and March 2020, 20 patients underwent TAMIS at one center. The median age of the patients was 67 (37-79). The procedure was performed in all of the patients with a lithotomy position. Full-thickness defect after complete resection of the lesion was observed in 5 (25%) patients. However, abdominal cavity was not exposed through the TAMIS procedure in any of the patients. The rectal wall defect was not repaired in any of the patients. No major complication occured in the patients. The hospital stay was 1 (1-4) days. The surgical margin was negative in 19 patients (95%). After the follow-up period of 9 (1-43) months, 3 (17%) patients had a recurrence and further surgery was performed. Conclusion: TAMIS using SILS port for the management of rectal neoplasms is a safe and effective for treatment benign rectal lesions.

Amaç: Benign rektal neoplazmların tedavisi için geleneksel transanal eksizyon on yıllar önce tanımlanmıştır. Bununla birlikte, bu tekniğin zorlukları, alternatif yaklaşımların kullanılmasına yol açar. Bu çalışmada benign rektal neoplazmların tedavisinde tek insizyon laparoskopik cerrahi (SILS) portu ile transanal minimal invaziv cerrahi (TAMIS) sonuçlarını değerlendirdik. Yöntem: Merkezimizde SILS portu ile TAMIS uygulanan benign rektal neoplazmalı hastaların verileri retrospektif olarak incelendi. SILS portu anal kanal içerisine yerleştirildi ve tümörlerin eksizyonu için ultrasonik mühürleme cihazı kullanıldı. Ameliyat sırasında veya sonrasında komplikasyonlar rapor edildi. Hastalar proktoskopi ve rektal muayene ile takip edilerek nüksler değerlendirildi. Bulgular: Temmuz 2015 ile Mart 2020 arasında 20 hastaya TAMIS uygulandı. Hastaların ortanca yaşı 67 (37-79) idi. Tüm hastalarda litotomi posizyonunda ameliyat edildi. 5 (%25) hastada lezyonun tam olarak çıkarılmasından sonra tam kat defekt görüldü. Ancak hiçbir hastada abdominal boşluğa girilmedi. Hiçbir hastada rektal duvar defekti onarılmadı. Hastalarda majör komplikasyon izlenmedi. Hastanede kalış süresi 1 (1-4) gündü. 19 hastada (%95) cerrahi sınır negatifti. 9 (1-43) aylık takip süresinden sonra 3 (%17) hastada nüks görüldü ve ileri cerrahi yapıldı. Sonuç: Rektal neoplazmların yönetimi için SILS portunu kullanılan TAMIS, benign rektal lezyonların tedavisi için güvenli ve etkilidir.
SİLS Port Kullanılarak Yapılan Transanal Minimal İnvaziv Cerrahi (TAMIS): Tek Merkez Kısa Dönem Sonuçları
Keywords: Rectal adenoma; single-incision laparoscopic surgery port; TAMS; Rektal adenom; transanal minimal invaziv cerrahi; TAMİS